2015
DOI: 10.1186/s12879-015-1183-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of abacavir-containing combination antiretroviral therapy as first-line treatment of HIV infected children and adolescents: a systematic review and meta-analysis

Abstract: BackgroundAbacavir is one of the recommended nucleoside reverse transcriptase inhibitors (NRTIs) for the treatment of HIV infections among children and adolescents. However, there are concerns that the antiviral efficacy of abacavir might be low when compared to other NRTIs especially among children. There are also concerns that abacavir use may lead to serious adverse events such as hypersensitivity reactions and has potential predisposition to developing cardiovascular diseasesMethodsWe searched four electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Studies show that insu cient or low literacy is linked to low levels of protective behaviour and can eventually lead to vaccine hesitancy (Biasio, 2017;. Our ndings here also re ect previous studies across Africa, suggesting that residents with low adult literacy have lower acceptance of vaccination (Adetokunboh et al, 2015;Adamu et al, 2021). Vaccination messaging should be target-driven.…”
Section: Discussionsupporting
confidence: 84%
“…Studies show that insu cient or low literacy is linked to low levels of protective behaviour and can eventually lead to vaccine hesitancy (Biasio, 2017;. Our ndings here also re ect previous studies across Africa, suggesting that residents with low adult literacy have lower acceptance of vaccination (Adetokunboh et al, 2015;Adamu et al, 2021). Vaccination messaging should be target-driven.…”
Section: Discussionsupporting
confidence: 84%
“…This RCT compared the NRTIs ABC, AZT and d4T in HIV-infected African children, and found that all three NRTIs had similar outcomes in terms of clinical, immunological and virological responses (9). A finding by Adetokunboh et al also concluded that ABC based regimen in children had similar efficacy and safety profile with AZT based regimens (24). In contrary, the PENTA-5 trial demonstrated greater efficacy of ABC based regimen over AZT (16).…”
Section: Discussionmentioning
confidence: 99%
“…This RCT compared the NRTIs ABC, AZT and d4T in HIV-infected African children, and found that all three NRTIs had similar outcomes in terms of clinical, immunological and virological responses [11]. A finding by Adetokunboh et al also concluded that ABC based regimen in children had similar efficacy and safety profile with AZT based regimens [25]. In contrary, the PENTA-5 trial demonstrated greater efficacy of ABC based regimen over AZT [18].…”
Section: Discussionmentioning
confidence: 99%